Brand personality and identity in creating emotional relationship with consumer a study of the lifestyle patterns among affluent polish urbanites - Czarnota Monika (My University, 2008)
This thesis focuses on managing emotional connections between products and consumers and presents how the companies might use them as a way to maintain and build their brands. The author documents how people tend to subordinate their lives to brands, build on them their identity and self-confidence, as well as their feeling of stability and security. To demonstrate how brands work in the real world she illustrates each section with insights from top business leaders and she conducted research on 115 residents of Warsaw. In my research the author intended to prove the thesis that people need to put the masks that brands impose on them to feel more self-confident and safe. It allows them to define their own identity through gaining the acceptance of the group about the acceptance of which they really care. Furthermore, the aim of the research is to show that people treat a brand not only as a person but also as a friend. The study intends to explore the thesis above, and what is more, show that we can divide people in four different groups on the basis of their attitude towards brands and this is directly related withtheir personality as well as lifestyles. The research focuses on the mentioned group called “trendsetters” because they illustrate best the assumed thesis and most importantly this is the social class which members of the three other groups aspire to and admire.
Osobowość oraz tożsamość marki jako podstawowy element emocjonalnych więzi pomiędzy konsumentem a firmą - badanie wpływu marki na styl życia zamożnych Polaków
Keywords: brand; identity; brand positioning; brand-based culture; marketing